Evaluation of New prepared Culture Media for Cultivation and Identification of Escherichia coli and its Strain O157: H7. - Issa, Mohsen Ayoub (Journal of agricultural, environmental and veterinary sciences, 2018)
E.coli is the most important bacteria in health and environmental terms, which cause a wide range of diseases spread globally, especially in developing countries, which requires continuous research to improvement different diagnosis methods of these bacteria. The idea of ​​this research was the use of fish meat and dates to prepare specialized culture media for these bacteria and their strains. Results of growth test of different isolates on prepared liquid media showed that the best growth was in medium prepared of fish and dates extracts together, it was superior to the standard medium Nutrient broth. It was superior to MacConkey broth and Lauryl tryptose broth as standard media in detection of bacteriological contamination of water after showed medium color change and gas production during (9, 6) hours only, respectively. Differential solid culture medium for E. coli also was prepared similar to MacConkey agar characteristics, the colonies of this lactose fermenting bacteria were pink compared to non- fermented Salmonella spp pale colonies. Other differential solid culture medium for E.coli O157: H7 strain was prepared according to inability of this strain to ferment sorbitol sugar and the addition of phenol red dye, the medium appeared clear differentiation between this strain and other sorbitol fermented isolates that changed the medium color to yellow.
Keywords: culture media; fish meat; dates; O157: H7 E.coli